The Essence of Citizenship Education in Building Students' Democratic Attitude at Cinta Kasih Primary School - Lubis, Aminah; Silalahi, Yulianda Ghrace; Sihombing, Evi Ariyanti Marlina; Yunita, Sri; Ndona, Jacobus (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This research aims to explore and analyze the role of Citizenship Education (PKn) in forming students' democratic attitudes at Cinta Kasih Elementary School. The research method used is descriptive qualitative with a literature study approach that refers to journals, books and other sources that are relevant to the research topic. Through analysis of the content of selected literature, this research identified several important aspects of Civics that play a role in fostering students' democratic attitudes at Cinta Kasih Elementary School. These aspects include: introduction to the concept of democracy, formation of political awareness, development of participation skills, respect for pluralism and diversity, learning through experience, and student empowerment. It is hoped that the results of this research will provide a deeper understanding of the importance of Civics in developing students' democratic attitudes, as well as provide a basis for developing a more effective Civics curriculum and learning strategy at Cinta Kasih Elementary School.